Team Work, Openness of Communication and Working Period for Reporting Patient Safety Events at the Regional General Hospital dr. ISKAK Tulungagung - Dara Benedicta Antoninda; Indasah (Journal Of Nursing Practice, 2023)
Background: In 2021 RSUD Dr. Iskak Tulungagung again adopted a patient safety culture measure that was implemented for all hospital staff from several sources as the first step in a good patient safety program. Nurses are a component of human resources (HR) in the hospital health care system, who work directly on the front lines and have more time to deal with patients. Purpose: The purpose of this study is to analyze the influence of team work, communication openness and tenure on patient safety incident reporting at dr. ISK Tulungagung. Methods: The type of research conducted in this activity is an observational study with a cross-sectional design and using logistic regression statistical tests. The sample in this study were 406 respondents. Results: Based on the characteristics of the respondents, it showed that there were 304 female nurses and 102 male nurses. The longest working period was 6-10 years, namely 196 people. The results of the descriptive analysis show that the value of team work is 85%, the value of open communication is 83% and the cultural value of reporting patient safety incidents is 94%. Meanwhile, based on the statistical test results, the p-value is 0.001 <0.05; p-value 0.001 <0.05; and a p-value of 0.000 <0.05. Conclusion: Thus showing that there isThe Influence of Team Work, Open Communication and Working Period on Reporting of Patient Safety Incidents at the Regional General Hospital dr. ISK Tulungagung.